2017
DOI: 10.1039/c6ob02657e
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis and biological activity of dolastatin 16

Abstract: The total synthesis of dolastatin 16, a macrocyclic depsipeptide first isolated from the sea hare Dolabella auricularia as a potential antineoplastic metabolite by Pettit et al., was achieved in a convergent manner. Dolastatin 16 was reported by Tan to exhibit strong antifouling activity, and thus shows promise for inhibiting the attachment of marine benthic organisms such as Amphibalanus amphitrite to ships and submerged artificial structures. Therefore, dolastatin 16 is a potential compound for a new, enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Total synthesis of dolastatin 16 has been reported, and its potent antifouling activity towards barnacle cyprids conrmed. 632 Three studies reported on new biologically active analogues of the dolastatin 10 peptide scaffold. [633][634][635] Novel tambjamine analogues have been shown to activate the p38 MAPK pathway leading to in vitro and in vivo activity towards lung cancer cell lines.…”
Section: Molluscsmentioning
confidence: 99%
“…Total synthesis of dolastatin 16 has been reported, and its potent antifouling activity towards barnacle cyprids conrmed. 632 Three studies reported on new biologically active analogues of the dolastatin 10 peptide scaffold. [633][634][635] Novel tambjamine analogues have been shown to activate the p38 MAPK pathway leading to in vitro and in vivo activity towards lung cancer cell lines.…”
Section: Molluscsmentioning
confidence: 99%
“…The loss of activity was attributed to either an unidentifiable contaminat or a solvent-induced conformational change associated with the synthetic compound. On a more encouraging note, the Matsuda group synthesized dolastatin-16 and found it to be a potent antifouling agent against Amphibalanus amphitrite , 29 suggesting that a lack of cancer cell inhibition may not be the end of the development prospects of dolastatin-16.…”
Section: Discussionmentioning
confidence: 99%
“…More encouragingly, field testing of dolastatin 16 was conducted at concentrations of 10.0, 1.0, 0.1, and 0.01 μg/mL, respectively, and the barnacle counts of all dolastatin 16-treated plates were obviously lower than that of the negative controls after 4 weeks, suggesting its potential application as an antifoulant [ 58 ]. Although its total synthesis was challenging due to its complex structure, dolastatin 16 has been recently successfully synthesized by Casalme et al [ 59 ]. The synthetic dolastatin 16 showed potent antilarval settlement of B. amphitrite similar to that of natural dolastatin 16, which further supported that dolastatin 16 might be explored as a candidate antifoulant.…”
Section: Nucleosides and Peptidesmentioning
confidence: 99%